Location-inventory-routing model for vaccine distribution problem with heterogeneous fleet - Tasdemir, Beste Desticioglu; Simsek, Ahmed Ihsan; Koç, Erdinç (Inderscience Publishers, 2025)
In this study, the vaccine distribution problem of the health directorate of the province of Elazig in Turkey was examined. The study’s model was developed under the presumption that the province of Elazig’s vaccine distribution fleet is heterogeneous. Vaccines were delivered to all demand points from both warehouses by vehicles with different capacities. A mathematical model is proposed that aims to minimise the distance travelled. Considering the characteristics of the vehicles used in the distribution, speed and working hour’s constraints were added to the model. The proposed mathematical model for the distance constrained heterogeneous fleet vehicle routing problem has been implemented as two different central distribution centres. There is only one kilometre difference between the total distance travelled by the vehicles delivering vaccines from Fethi Sekin State Hospital and the provincial health directorate. However, vaccine distribution activities can be carried out with two vehicles from the provincial health directorate and one vehicle from Fethi Sekin State Hospital. According to the results obtained, it can be stated that Fethi Sekin State Hospital is the appropriate point for storage. Copyright © 2025 Inderscience Enterprises Ltd.
Keywords: inventory-routing; mathematical model; routing problem; vaccine distribution